1996
DOI: 10.1152/ajprenal.1996.270.5.f822
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific effects of epoxyeicosatrienoic acids on renal vascular tone and K(+)-channel activity

Abstract: The present study examined the effects of 11,12- and 14,15-epoxyeicosatrienoic acids (EETs) on the diameter of small renal arteries of the rat and assessed their action on K(+)-channel activity in vascular smooth muscle (VSM) cells isolated from these vessels. The R,S-isomer of 11,12-EET (1, 10, and 100 nM) increased the diameter of small renal arteries preconstricted with phenylephrine; however, the S,R-isomer was inactive. Both the R,S- and S,R-isomers of 14,15-EET had little effect on the diameter of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
151
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(164 citation statements)
references
References 0 publications
11
151
1
Order By: Relevance
“…These compounds have been reported to play an important role in the control of both renal tubular and vascular function (26). EETs are potent endothelial-derived vasodilators in the renal circulation (17,47). They also inhibit sodium and water reabsorption in the collecting duct (40).…”
mentioning
confidence: 99%
“…These compounds have been reported to play an important role in the control of both renal tubular and vascular function (26). EETs are potent endothelial-derived vasodilators in the renal circulation (17,47). They also inhibit sodium and water reabsorption in the collecting duct (40).…”
mentioning
confidence: 99%
“…In renal tubules 20-HETE inhibits Na ϩ -K ϩ -ATPase, a Na ϩ -K ϩ -2Cl Ϫ cotransporter, and 70-pS K ϩ channels, leading to natriuresis and diuresis (3,30,38). EETs and DHETs are generally considered vasodilatory, although they exhibit both vasodilatory and vasoconstrictive properties in vitro, depending on the vascular bed and species that are studied (20,55,57). A number of studies suggest that EETs are endothelium-derived hyperpolarizing factors that mediate vasodilation by activation of Ca 2ϩ -dependent K ϩ channels in vascular smooth muscle cells (6,7,10).…”
mentioning
confidence: 99%
“…Consistent with this later observation, we have recently reported that the various EETs induce stereospecific dilation of renal arterioles (Ͻ50 m) in the nanomolar concentration range, which is mediated through activation of a large-conductance Ca 2ϩ -activated K ϩ channels in rat renal arteriolar smooth muscle cells. 21 These findings appear to indicate that the EETs are more potent in dilating resistance-sized vessels than large arteries.…”
Section: Selected Abbreviations and Acronymsmentioning
confidence: 91%
“…22 EETs released from astrocytes potently dilate cerebral microvessels by enhancing outward K ϩ current and hyperpolarizing cerebral and other arterial muscle cells. 2,4,21,24 Thus, a hypothesis emerges which states that release of glutamate during normal neuronal activity can bind to glutamate receptors on astrocytes to increase AA turnover and release EETs from astrocytes that quickly and potently dilate the cerebral microcirculation to "shunt" flow to those areas surrounding metabolically active neurons. This hypothesis is depicted in Fig 5. Binding of glutamate can activate phospholipases to release AA from the membrane of astrocytes, and free AA can be metabolized by P450 epoxygenases to EETs, which can diffuse out of astrocytic foot processes and hyperpolarize cerebral arterial vascular smooth muscle and induce dilation.…”
Section: Glutamate-induced Release Of Eets May Mediate Functional Hypmentioning
confidence: 99%